Reproductive Aspects of Scad Fish (Decapterus macarellus) Landed at The Fish Landing Base of Tanjung Luar, East Lombok - Winata, I Gede Darma; Karnan, Karnan; Mahrus, Mahrus (Jurnal Biologi Tropis, 2024)
Scad fish (Decapterus macarellus) is a fish of important economic value, this fish is the main target of fishermen in Tanjung Luar East Lombok but information about its existence biologically has never been research.This study intended to analyze the reproductive aspects of the scad fish landed at PPI Tanjung Luar, East Lombok, based on sex ratio, length-weight relationship, gonad maturity level, gonad weight, and Gonadosomatic Index (GSI). The sampling technique was quota  implemented to get 270 scad fish from March to May 2024. Simple regression linear was applied to analyze the relationship between length and weight of scad fish. This research showed that: 1) the sex ratio of scad fish in the study site was varied, that is  0.58:1; 0.88:1; and 0.58:1 for in March, April, and May respectively, 2) the growth pattern of scad fish in the study site is negative allometric, 3) the gonad's maturity stages dominated by stage of I and II, This shows that the kite fish is still in an immature condition. and 4) the gonadal somatic index indicates that the fish can spawn more than once a year.